Annual Plan Proposals 1980-81 State Planning Board Trivandrum - Planning Commission (Planning Commission, 1980)
The Draft Five Year Plan for Kerala submitted to the Planning Commission had envisaged an outlay of Rs. 2.000 crores in the State Sector for the five year period 1978-83. However, during the subsequent discussions between the State Government and the Planning Commission, the outlay was fixed at Rs. 1,200 crores taking into account the overall resource constraints. This reduction in the size of the State’s Five Year outlay will result in a slowing down of the rate of total investment in the State’s economy, since public sector outlay also performs the role of pace-setter in economic growth.
State Planning Board Trivandrum